Classification of Free Movement Papua as Unlawful Belligerent - Hutaepa, Sintong Arion (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
In recent years, the OPM has carried out a massive movement in attacking and killing civilians in Papua. This action was deemed appropriate because of the OPM's position as a legal subject in accordance with international law. The aim would measure how much far OPM's position as for fulfil elements as a subject of international law based on international treaty and customs international. This article categorized as normative legal research whose using positive law. Normative legal research using secondary data consisting of from primary law including national regulations nor international law including international treaty and customs international related about OPM as unlawful belligerent. The Indonesian government classifies the OPM as a KKB with the label of a terrorist group. IHL subjects need to meet certain conditions to be counted as combatants. OPM does not meet the specified conditions so that it is counted as unlawfully belligerent. This condition makes the OPM unable to enjoy treatment like a combatant during an armed conflict.